Building A Theoretical Research Model for Trust Development: The Case of Mobile Financial Services in Myanmar - Tun, Phyo Min (The South East Asian Journal of Management, 2020)
Research Aims - This research study focuses on the factors affecting customer trust in mobile financial services (MFS) in Myanmar by developing a research model that incorporates six different factors: perceived usefulness, perceived ease of use, social pressure, enabling conditions, service quality, and satisfaction. Design/Methodology/Approach - Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were employed to analyse the data. Subsequently, Structural Equation Modeling (SEM) was utilised to examine hypotheses. An analysis was performed on the survey data collected from 250 mobile phone users who are likely to use or currently using MFS in Myanmar. Research Findings - The results indicate that trust in MFS is significantly influenced by enabling conditions, service quality and satisfaction. The study also found that perceived usefulness, perceived ease of use and social pressure have statistically insignificant effects on trust-building in the MFS context. Theoretical Contribution/Originality - A finalised trust-development theoretical research model was formulated and proposed for utilisation in the investigation of customers’ trust in future research within a similar context. Managerial Implication in the South East Asian Context - The findings of this study are beneficial and valuable for Mobile Financial Services Providers (MFSP) in the ASEAN countries, enabling them to create suitable marketing strategies, business approaches and service infrastructures regarding their customers, thereby developing customer trust. Research Limitations and Implications - The conclusion is limited to the mobile financial services sector in Myanmar, and the opinions of non-adopters and rejectors are excluded.